A survey of vehicle topcoat colour frequency and chemical profiling of paint chips for forensic comparison - Jamal@A Jalal, Siti Noriha (2020)
Forensic examination of car paint related evidence collected from a crime scene could be used to link between people, objects and/or places. This study was aimed to investigate the vehicle topcoat colour frequency and the chemical profiling of paint chips for forensic comparison. The first phase of the study involved a survey of the vehicle topcoat colour in two areas within a day and with different days. Subsequently, the second phase involved analysis of paint chip samples obtained from the varying parts of the same car and different cars carrying the same topcoat colour using Attenuated Total Reflectance-Fourier Infrared (ATR-FTIR) spectroscopy. The survey showed that white, black, and light gray colours were the most common encountered vehicle topcoat colours in the research area, namely in Johor Bahru. Two vehicles with light gray colour and two vehicles of white colour are chosen for sampling regardless its brand for analysis. ATRFTIR spectroscopy result had successfully generated the profiles of the paint chips tested in this study. It was found that the ATR-FTIR profiles collected from the same car were shown to be very similar and located closely in the score plot. On the other hand, paint chips collected from different cars could have different profiles. From this study, it was noted that the topcoat colour determination by witness or victim, particularly related to vehicular accidents, shall be interpreted carefully to assist the forensic investigation and interrogation. It was also suggested that the colour information of a vehicle could serve as an initial lead for investigative team in tracing the vehicle. Paint chip samples were also very useful to differentiate the source of forensic evidence